REVIEW ON MANAGEMENT PREVENTION AND TREATMENT OF DIABETES MELLITUS - N, Nagoba Shivappa; V, Sugave Ramling; M, Ningule Ganesh; Y, Patil Pooja (Asian Journal of Pharmaceutical Research and Development, 2019)
Diabetes mellitus is the third leading cause of death (after heart disease and cancer) in many developed countries it affect about 6-8% of general population. The complication occurs in diabetes mellitus affect the eye, kidney and nervous system. Diabetes is major cause of blindness, renal failure and heart attack. And another is diabetes insipidus. India is the diabetes capital of the world. In India 50 million peoples suffering from type-2 diabetes. This country has major challenge & burden of economic condition to face. Because diabetes mellitus insulin therapy have higher cost & demand is more. But medical experts that timely detection and right management can go a long way in helping patients lead a normal life. That required to more demanding new drug that have need to develop more bioavailability and less toxicity of drugs. Oral hypoglycemic drugs these drugs lower blood glucose levels and are effective orally. Some natural antidiabetic drugs used in treatment of diabetes mellitus, gymnema, pterocarpus, Jamun, bitter guard etc.